The effect of Surround sound on embodiment and sense of presence in cinematic experience: a behavioral and HD-EEG study - Langiulli, Nunzio; Calbi, Marta; Sbravatti, Valerio; Umiltà, Maria Alessandra; Gallese, Vittorio (Frontiers in Neuroscience, 2023)
Although many studies have investigated spectators' cinematic experience, only a few of them explored the neurophysiological correlates of the sense of Presence evoked by the spatial characteristics of audio delivery devices. Nevertheless, nowadays both the industrial and the consumer markets have been saturated by some forms of spatial audio format that enrich the audiovisual cinematic experience, reducing the gap between the real and the digitally mediated world.The increase in the immersive capabilities correspond to the instauration of both the sense of Presence, the psychological sense of being in the virtual environment, and embodied simulation mechanisms. While it is well known that these mechanisms can be activated in the real world, it is hypothesized they may be elicited even in a virtual acoustic spatial environment and could be modulated by the acoustic spatialization cues reproduced by sound systems. Hence, the present study aims to investigate the neural basis of the sense of Presence, together with the Emotional and Physical Involvement, evoked by different forms of mediation by testing different acoustic space sound delivery (Presentation modes: Monophonic, Stereo and Surround). To these aims, a behavioral investigation and a high-density electroencephalographic (HD-EEG) study have been developed. A large set of ecological and heterogeneous stimuli extracted from feature films were used. Furthermore, participants were selected following the Generalized Listener Selection procedure. We found a significantly higher event-related desynchronization (ERD) in the Surround Presentation mode when compared to the Monophonic Presentation mode both in Alpha and Low Beta centro-parietal clusters. We discuss thisthe results as an index of embodied simulation mechanisms that could be considered as a possible neurophysiological correlate of the instauration of the sense of Presence.